2007
DOI: 10.1007/s11064-006-9249-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of SelegilIne in Oxidative Stress Induced by Iron Neonatal Treatment in Rats

Abstract: Increased levels of iron in specific brain regions have been reported in neurodegenerative disorders. It has been postulated that iron exerts its deleterious effects on the nervous system by inducing oxidative damage. In a previous study, we have shown that iron administered during a particular period of the neonatal life induces oxidative damage in brain regions in adult rats. The aim of the present study was to evaluate the possible protective effect of selegiline, a monoamino-oxidase B (MAO-B) inhibitor use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Previous studies performed by our research group have shown that neonatal iron treatment induces lipid peroxidation and increases mitochondrial superoxide generation in the hippocampus, cortex, and substantia nigra 6,34 and protein carbonylation in the substantia nigra 35 in adult rats. In line with the present results, in previous studies we have also observed an increase in the apoptotic markers, Caspase 3 13 and Par4 12 in the brains of iron-treated rats.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies performed by our research group have shown that neonatal iron treatment induces lipid peroxidation and increases mitochondrial superoxide generation in the hippocampus, cortex, and substantia nigra 6,34 and protein carbonylation in the substantia nigra 35 in adult rats. In line with the present results, in previous studies we have also observed an increase in the apoptotic markers, Caspase 3 13 and Par4 12 in the brains of iron-treated rats.…”
Section: Discussionmentioning
confidence: 70%
“…Brain regional biochemical analyses in the 34 preclinical studies most frequently investigated oxidative stress, neurochemical markers, or iron levels. Markers of brain oxidative stress, including malondialdehyde and protein carbonyls, were increased in 9 studies 34 , 49 , 55–58 , 63–65 ; the 1 study that assessed glutathione levels found no change. 66 Six studies assessed the effects of neonatal iron intake on brain neurochemistry outcomes.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies proposed that selegiline, a selective irreversible MAO-B inhibitor, is able to reduce the TBARS levels in rat brain tissue ( 37 , 38 ) . In the present study, it was demonstrated that there is a positive correlation between brain MAO activity and lipid peroxidation of brain and liver (Table 3).…”
Section: Discussionmentioning
confidence: 99%